A Case of Soft Tissue Ossifications: A Case Report. Issue 2 (April 2019) - Arrigoni, Paolo; Minen, Alessandro
Abstract : Case: A patient who had previously been diagnosed with fibrodysplasia ossificans progressiva was seen for hip pain and progressive soft tissue ossifications. Through a careful clinical examination, by which a subtype of brachydactyly was noted, the Albright hereditary osteodystrophy phenotype was recognized, and a new diagnosis of pseudopseudohypoparathyroidism was established. This paucisymptomatic condition often remains unidentified; however, its transmission can lead to more potentially serious diseases. Conclusions: A careful diagnostic process, including physical examination, is essential. Even if advanced tests exist, small clinical findings can lead to the proper conclusion. In our case, a finger pointed us in the right direction.